SISTEM KEPENDUDUKAN DESA BERBASIS WEB PADA DESA CIHUNI KECAMATAN PAGEDANGAN KABUPATEN TANGERANG - Angelina Efrida Purba; Catur Putro Utomo; Nurjamin Nurjamin (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2017)
The development of computerized systems can not be separated from technological developments which can affect many aspects of human life. One of the advantages of the computerized system is to produce a system that is relevant, timely and accurate. Build a village settlement system requires a good understanding and clear about the system to be used both in the procedures of the system, input, output and the things that affect system performance both for short term and long term. One of them in the population data. In the village Village Cihuni done today by using a manual system. Examples such as demographic data. So frequent errors in process or keep a record of the population, because in pengolahanya still with the conventional process. it is proposed to build an application in the form of settlement system that can be used by the village staff to process all web-based demographic data. It is expected that these applications can help in addition to demographic data processing can also store data properly and facilitate the public in terms of service needs Letter.